2010
DOI: 10.1002/cne.22509
|View full text |Cite
|
Sign up to set email alerts
|

Stereocilin connects outer hair cell stereocilia to one another and to the tectorial membrane

Abstract: Stereocilin is defective in a recessive form of deafness, DFNB16. We studied the distribution of stereocilin in the developing and mature mouse inner ear and analyzed the consequences of its absence in stereocilin-null (Strc −/− ) mice that suffer hearing loss starting at post-natal day 15 (P15) and progressing until P60. Using immunofluorescence and immunogold electron microscopy, stereocilin was detected in association with two cell surface specializations specific to outer hair cells (OHCs) in the mature co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
99
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 34 publications
(60 reference statements)
11
99
0
Order By: Relevance
“…This might explain observations that loss of top connectors substantially affects cochlear non-linearity (Verpy et al, 2011). It has also been reported that the top connectors may function to reduce viscous drag on the bundle (Kozlov et al, 2011).…”
Section: Lateral Linksmentioning
confidence: 77%
See 4 more Smart Citations
“…This might explain observations that loss of top connectors substantially affects cochlear non-linearity (Verpy et al, 2011). It has also been reported that the top connectors may function to reduce viscous drag on the bundle (Kozlov et al, 2011).…”
Section: Lateral Linksmentioning
confidence: 77%
“…The contact region is shown, an area that may coincide with a region of 'top connectors' but in mammals also appears to label with antibodies to amiloride sensitivity sodium channels (Hackney et al, 1992). Another region of top connectors is the lateral links at the tip of the tallest stereocilia, some of which extend into the overlaying tectorial membrane (Verpy et al, 2011). Scale bars: A53 mm; B5600 nm; C550 nm; D5100 nm; E and F5250 nm.…”
Section: Deflectionmentioning
confidence: 99%
See 3 more Smart Citations